Sex Differences in Wellness Scores in Collegiate Athletes - Jennifer A Bunn; Michael R Jiroutek (Journal of Coaching and Sports Science, 2024)
Subjective wellness scores reflect athlete responses to training, fatigue, personal experiences, and recovery, and evidence suggests these scores may differ between athletes based on sex. This study aimed to evaluate the differences in daily wellness scores between sexes in collegiate soccer, swimming, and basketball athletes. Athletes (n = 294, 63 percent female) completed daily wellness surveys for energy, health status, mood, muscle readiness, sleep quality, sleep duration, stress, diet, and overall wellness. Variables were evaluated on a 5-point Likert scale, except sleep duration, quantified in hours. Repeated measures, mixed linear models, repeated measures, and ordinal logistic models were used to assess sex differences in wellness outcomes. In basketball, females have 0.30 times the odds (95 percent CI 0.19, 0.48) of males of a worse health status score. For soccer, females have 2.45 times the odds (95 percent CI 1.32, 4.44) of males with a worse stress wellness score. In swimming, females, on average, slept 0.40 more hours of sleep per night (95 percent CI 0.02, 0.79) as compared to males. These data suggest that differences in wellness subcomponents are nuanced by sport. This information can be used to provide targeted programming for athletes to improve wellness and reduce stress, which may subsequently enhance mental health, academic performance, and sports performance.